APLICABILIDADE DO CONCRETO RECICLADO COMO ALTERNATIVA PARA A CONSTRUÇÃO CIVIL (REMUNOM, 2025)
Given the increasingly evident environmental impacts caused by civil construction activities, the adoption of sustainable strategies that help reduce the exploitation of natural resources and waste generation becomes imperative. In this context, the present article investigates the feasibility of recycled concrete as a sustainable and technically efficient solution for the construction sector. The analysis focuses on the properties of recycled aggregates derived from construction and demolition waste (CDW), comparing their performance with that of conventional materials. Topics such as mechanical strength, durability, economic viability, and environmental impacts are addressed, along with the limitations and potential applications in various types of projects. The findings show that, when properly processed and applied, recycled concrete can meet regulatory requirements, significantly contributing to the mitigation of environmental impacts and to the advancement of a circular economy in the construction industry.